Energy Intake, Protein Intake, and Toddler Hygiene with the Incidence of Stunting in 24-59 Months Toddlers in Mentawai Islands - Ilmiati, Fatia; Syauqy, Ahmad; Noer, Etika Ratna; Margawati, Ani; Kartini, Apoina (JURNAL INFO KESEHATAN, 2024)
Toddlerhood is an important period in human growth and development; during that period, if the nutrition is not adequate, they risk stunting. Some factors that cause this are energy intake, protein intake, parenting, and food security. In 2022, the prevalence of stunting is around 148 million (22.3%), most coming from Asia and Africa; according to WHO, in Indonesia, the prevalence of stunting is 21.6%. The incidence of stunting in Mentawai Islands Regency is 32%, the second highest rate below the national rate. According to the author's knowledge, this research is the first study to analyze the relationship between independent and dependent variables as well as the determinants of stunting in toddlers in the Sarereiket Health Centre using questionnaire data, direct observation, and interviews that have gone through a validation and reliability process from experts through the laboratory. The research aims to analyze the relationship between energy intake, protein intake, and hygiene of toddlers and the incidence of stunting in toddlers aged 24-59 months in South Siberut District, Mentawai Islands Regency. The method used the observational method. The subjects of analysis were 393 toddlers aged 24-59 months in the Sarereiket Health Centre who were involved in this study. Multivariate regression was performed to identify the relationship between dependent and independent variables. The results indicate that toddlers' energy intake, protein intake, and hygiene are associated with stunting. The results of the multivariate analysis in this study indicate that protein intake and toddler hygiene influence stunting and contribute to increasing the incidence of stunting in toddlers. The conclusion is there is a significant relationship between energy intake, protein intake, and hygiene of toddlers and the incidence of stunting in the Sarereiket Community Health Centre, Mentawai Islands.